Predictors of Stunting Occurrence in The First 1000 Days of Life Based on Characteristics of Mother and Child - Arda Dinata; Salahuddin Al Ayubi; Endang Puji Astuti; Toto Sudargo; I Made Alit Gunawan (HIGIENE: Jurnal Kesehatan Lingkungan, 2021)
The effort to reducing the prevalence of stunting continue to be done especially on 1000 the first days of life in order to prevent the emergence of the impact of stunting in the period of the next life. Pregnant women, breast-feeding mothers, newborns and children aged under two years (baduta) target group is to improve the quality of life at 1000 the first days of life.This study was know the risk factors that relating to characteristics 1000 maternal and child in the period of the first days of life to events stunting of children aged 6-24 months in Katingan Regency. Research observational design control unmatched case study by approaching retrospective. The subject of study you are the 6-24 meet the criteria of the inclusion of 100 baduta stunting (TB/U < -2 SD) and 100 baduta normal (TB/U ≥ -2 SD) in Katingan Regency. Based on the results of the analysis bivariat characteristic of a mother and children a factor is risk stunting nutritional status of early pregnancy (p=0.047; OR=1.95), the status KEK (p=0.018; OR=2.15); the increase in weight for pregnant (p=0.56; OR=1.18); the frequency of monitoring growth (p=0.637; OR=1.24); the handling of childbirth (p=0.825; OR=1.1); IMD (p=0.159; OR=1.55); breastfeeding exclusive (p=0.145; OR=1.53); and frequency monitoring growth (p=0.08; OR=1.66). With logistic regression multivariate analysis shows that there is no variable free directly influence to events stunting. The results the analysis there was no correlation welfare between a gestation period of the baduta age to stunting. Characteristic of a mother and child that has an effect greater as the stunting is increasing weight of pregnant mothers during pregnancy because it has the largest statistics z (0.867). Efforts to prevent and reduce stunting must be implemented in all the period of 1000 HPK (pregnancy, childbirth, and the age of baduta).